Developing Interactive Multimedia of Acid-Base Titration Practicum for Science Students of Institut Studi Islam Sunan Doe - Urwatil Wutsqo Amry (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2025)
As a newly established campus, Sunan Doe Institute possesses a lot of lackings; one of them is that there is no laboratory available for the Faculty of Tarbiyah and Tadris up until now. The unavailability of this laboratory has a lot of influence on the practicum skills and experience of science students, especially the students of Chemistry department and science department. Chemistry is a branch of science that studies concepts at the macroscopic, submicroscopic and symbolic levels. This characteristic reinforces that chemistry learning requires supporting facilities in the form of a laboratory. One of the materials that involves the comprehension of macroscopic, microscopic and symbolic material is the concept of acid-base titration. The unavailability of laboratories at Sunan Doe Institute requires lecturers to provide alternative learning media that can provide practicum experience in the laboratory. One of the media that can provide practicum experience and can give students active participation in its usage is interactive multimedia. This research used the 4D research and development model developed by Thiagarajan. The results of the product assessment by material experts obtained a percentage of 90.80% with a valid category and no need for revision. Media experts gave a score of 96.19% in the valid category and no need for revision. The results of the small group trial were 90.78% in the valid category and did not need revision. Based on these results, the interactive multimedia acid-base titration developed was declared valid and suitable to be used in learning activities.